(untitled) (Signifiances (Signifying), 2019)
We situate our approach in the paradigm of enaction (Varela et al., 1991) which postulates that all cognition operates through movement in a context of body-environment interactions. The aim of this article is to rethink Saussure’s sign theory (1916/1996), presented as disembodied and decontextualized, in the light of this recent paradigm, following Bottineau (2012a, b, c, d; 2017A, b, c). For this we use the Theory of Submorphemic Saliencing (Grégoire, 2012a, 2014; 2015; 2017a, b, c, d) which postulates that the enaction of meaning in discourse is based on a simplex (Berthoz 2009) and vicariant (Berthoz 2013) behavior of biocultural actions saliencing. We will first propose a terminology for distinguishing between first-order linguistic actions and second-order linguistic units, which appears fundamental for any approach to the saussurean notions of sign, signifier and signified.